Răspuns :
[tex]2 {x}^{2} - 3x + 1 = 0[/tex]
[tex]2 {x}^{2} - 2x - x + 1 = 0[/tex]
[tex]2x(x - 1) - 1(x - 1) = 0[/tex]
[tex](2x - 1)(x - 1) = 0[/tex]
[tex] = > 2x - 1 = 0 \: \: sau \: \: x - 1 = 0[/tex]
[tex]2x - 1 = 0[/tex]
[tex]2x = 1[/tex]
[tex]x = \frac{1}{2} [/tex]
[tex]x - 1 = 0[/tex]
[tex]x = 1[/tex]
S={1/2;1}
[tex]\it 2x^2-3x+1=0 \Rightarrow 2x^2-2x-x+1=0 \Rightarrow 2x(x-1)-(x-1)=0 \Rightarrow \\ \\ \Rightarrow (x-1)(2x-1)=0 \Rightarrow \begin{cases} \it 2x-1=0 \Rightarrow x_1=\dfrac{1}{2}\\ \\ \it x-1=0 \Rightarrow x_2=1\end{cases}[/tex]